Laparoscopic removal of transmigrated intrauterine contraceptive device from abdomen in an asymptomatic patient - Bhageerathy, Pallipuram S.; Singh, Scott A.; Dhinakar, Manjula; Lukose, Jose M. (International Journal of Research in Medical Sciences, 2018)
Uterine perforation followed by transmigration of intrauterine contraceptive device to the abdominal cavity is one of the rarest, but most dangerous complication of Copper T. These displaced Copper containing devices can cause chronic inflammatory reaction leading to adhesions, intestinal obstruction and even bowel perforation. Hence removal of these devices once found outside the uterus is recommended. Traditionally, a laparotomy used to be performed owing to the associated inflammation, adhesions and the risks of bowel injury. Laparoscopic removal of these displaced devices is a minimally invasive surgical approach with good results in skilled hands. Authors reported a rare case of misplaced transmigrated intrauterine contraceptive device in a 43-year-old asymptomatic lady. The Copper T had migrated after silent perforation of the uterus and was impacted in the greater omentum. There was evidence of chronic inflammation and small pockets of pus surrounding it. There were flimsy bowel adhesions. The dislodged device was successfully removed laparoscopically along with partial omentectomy without any complications. Regular follow up of patients who have had Copper T insertions and teaching them to feel the thread and report if not felt is essential to diagnose complications early. A transmigrated intrauterine device can be successfully removed laparoscopically.